LONG-TERM TRENDS OF THE MAIN BLOOD LIPID PARAMETERS IN SIBERIAN POPULATION - Yu. P. Nikitin; S. K. Malyutina; K. V. Makarenkova (Кардиоваскулярная терапия и профилактика)
Aim. To carry out the population analysis of blood lipid profile trends during the period from 1985 to 2005 in Novosibirsk population.Material and methods. The study was carried out based on the databases of two large international epidemiological projects done in Novosibirsk, WHO “MONIСA” and “HAPIEЕ”. The representative samples from nonorganized population of Novosibirsk were tested in compliance with protocol of the projects. The analysis included data of 10272 people aged from 45 to 64 years; among them 4783 were men and 5489 — women.Results. Blood TC, non-HDL–C and LDL–С levels from the citizens of Novosibirsk aged 45–64 were significantly lower in the year 1995: 5,50±0,03 mM/l, 4,07±0,03 and 3,48±0,03 mM/l, respectively. By 2005 these values increased significantly and became higher than those initial in 1985. For women 20-year changes in TC, non-HDL–C and LDL–С levels are more prominent than for men. Trends of blood triglyceride levels are analogous to the changes of the indexes described above: average levels were the lowest in 1995 and the highest — in 2005. During a twenty years period the gradual statistically significant increase of blood HDL–C concentrations was noted: in 1985 its concentration was 1,29±0,01 mM/l, in 1995–1,42±0,01 mM/l (p<0,001), in 2005–1,53±0,004 mM/l (p<0,001). HDL–C level for the first decade (1985–1995) increased at average by 10% for the all tenyear period, and for the twenty-year period — by 18,6%, at that for men the increase was more significant (20,2%) than for women (16,4%). By 1995 the absolute values of atherogenicity coefficient decreased significantly; for women in a greater degree. By 2005 the correlation of pro-atherogenic factor to atherogenic one has slightly increased however stayed lower in relation to 1985.Conclusion. In the year 1995 in Siberian population blood TC, non-HDL–C, LDL–С and TG levels appeared to be lower than in 1985 and 2005. Blood HDL–C content was increasing with each decade. Atherogenicity coefficient decreased during the first decade (by 1995), and during the subsequent years slightly increased for women, but did not change significantly for men.